Patenting Proteomics Patentability and Scope of Protection of Three-Dimensional Protein Structure Claims under German, European and US law - Schuster, Martina (Munich Intellectual Property Law Center - MIPLC, 2010)
The Human Genome Project revealed that the human organism contains far fewer genes than proteins. The fact that approximately 33,000 genes encode more than 200,000 thousands proteins invalidated the long-held assumption that one gene encodes a single protein. Further studies demonstrated that even small structural variations in the